Volcano Project Design: Innovation In Geoscience Learning - Hariyono, Eko; Prahani, Binar Kurnia; Mardiyanti, M. (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2020)
The research aim was to develop the Volcano Project Design (VPD) for improving the physics student research skills about volcano. The method used is a qualitative analysis where the research sample involves 34 undergraduate of physics students. The instrument used in VPD was equipped with the assessment format and rubric that was developed by researchers. The instruments tools were validated by experts in the field of geoscience and volcanology. The VPD guide contains the theoretical basis of fieldwork, descriptions of activities, project themes and targets to be achieved, phases of activities, and assessment of activities in the field. In addition, in the guidelines is also equipped with a guide of proposal preparation, field report and research products. The important results showed that the physics students were succeeded in conducting volcano research using VPD. This result was supported by the capabilities to identifying some crucial problems about volcanoes, presenting some solution based on several issues that have been identified and providing an accurate explanation of volcanic phenomena. The interesting finding based on research is the students’ research product as new information in geoscience. Even though needs intensive guidance, the product has an opportunity to be published broadly. Based on students’ perception, the program succeeded to build students' scientific attitude, constructing a positive value to the environment around the volcano and perfectly prepare students to help the community in the face of volcanic disasters.